From Hype to Reality: Exploring the Economic Impact of Cryptocurrency in the Archipelago - Firayani (PT. Anagata Sembagi Education, 2024)
This article examines the economic impact of cryptocurrency in the archipelago, focusing on shifting perceptions from hype to reality. Through a qualitative approach, the study uses in-depth interviews and content analysis from social media platforms to explore the views of the public, investors, and stakeholders on cryptocurrency. The findings suggest that despite significant investment potential and innovation opportunities, challenges such as unclear regulation, market volatility, and security risks remain major barriers to widespread adoption of cryptocurrency in Indonesia. The article suggests the need for more comprehensive policies and public education to maximize the economic benefits of this technology and mitigate its risks.